Cost-effectiveness of surgery versus cast immobilization for adults with a bicortical fracture of the scaphoid waist: an economic evaluation of the SWIFFT trial. (1st July 2021) - Hinde, Sebastian; Richardson, Gerry; Fairhurst, Caroline; Brealey, Stephen D.; Cook, Liz; Rangan, Amar; Costa, Matt L.; Dias, Joseph J.
Abstract : Aims: The aim of the Scaphoid Waist Internal Fixation for Fractures Trial (SWIFFT) was to determine the optimal treatment for adults with a bicortical undisplaced or minimally displaced fracture of the waist of the scaphoid, comparing early surgical fixation with initial cast immobilization, with immediate fixation being offered to patients with nonunion. Methods: A cost-effectiveness analysis was conducted to assess the relative merits of these forms of treatment. The differences in costs to the healthcare system and quality-adjusted life years (QALYs) of the patients over the one-year follow-up of the trial in the two treatment arms were estimated using regression analysis. Results: Our base case analysis found that patients randomized to early surgical fixation had statistically significantly higher mean costs to the NHS of £1, 295 more than for the cast immobilization arm (p < 0.001), primarily due to the cost of surgery. They also had a marginally better quality of life, over the period, of 0.0158 QALYs; however, this was not statistically significant (p = 0.379). The mean combined cost per additional QALY was £81, 962, well above the accepted threshold for cost-effectiveness used in the UK and internationally. The probability of early surgery being cost-effective in this setting was only 5.6%. Conclusion: Consistent with the clinical findings of SWIFFT, these results indicate that initial cast immobilization of minimally displaced scaphoid fractures, with immediate fixation only offered to patients with nonunion, is the optimal form of treatment, resulting in comparable outcomes with less cost to the healthcare system. Cite this article: Bone Joint J  2021;103-B(7):1277–1283.